Challenges of open dumping of animal wastes on the environment: A case study of S and D farms, Odeda, Nigeria - James Akintola; Balogun Lateef; Jude Abiola (African Journal of Environmental Economics and Management, 2017)
The study investigated the effect of open dumping of animal wastes on the farm workers’ health and the environment. The study employed Chi-Square’s test of result reliability revealed on hypothesis tests. The χ2 calculated value 0.013 for hypothesis I which is less than χ2 tabulated value of 3.84 at level of significance 0.05, indicates that the open dumping of animal wastes as a method of disposal has significant effect on health of the workers and the environment. Similarly for hypothesis II; χ2 calculated value of 0.06 is far less than the χ2 tabulated value of 3.84 at level of significance 0.05. This implies that level of waste disposal education of the workers significantly affects the method of disposal being employed on the farm. For the Hypothesis III; χ2 calculated value of 0.05 is also less than the χ2 tabulated value of 3.84 at level of significance 0.05, implying that the industrial training being given to the workers on waste disposal methods is not adequate.